A New Method for Measuring the Complex Permittivity and Permeability of Sintered Material FeSiAl Used for Microwave-Absorbing Load. Issue 1 (June 2020) - Zhang, Fang; Shen, Lianguan; Pei, Yuanji
Abstract: This paper describes a new method for measuring the complex permittivity and permeability of a sintered microwave-absorbing material. Thorough knowledge about microwave-absorbing materials is very important for the design and construction of accelerators. Although many methods of measuring the permittivity and permeability of a material have been developed and tested successfully, they are not suited to cases in which the microwave-absorbing material is coated on an oxygen-free high-conductivity copper (OFHC) surface by means of a special sintering technology. Thus, a new method is developed through a combination of testing and simulations. The complex permittivity and permeability of the microwave-absorbing material FeSiAl was obtained by this means, and a collinear load was designed based on the measurement results. The linear accelerator (LINAC) with the collinear load has been running well.